What I wish you knew : letters from our daughters' lives, and expert advice on staying connected (Middleton, WI : Pleasant, 2001)
Letters and the results of online surveys provide advice for parents of teenage girls on how to help their daughters deal with the many issues they face.
Includes bibliographical references (p. [212]-216) and index.
Adult
Adult
Keywords: Daughters; Mothers and daughters; Daughters; Mother-daughter relationship